2017
DOI: 10.5812/jjm.64269
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Toxins and Colonization Factors of Enterotoxigenic Escherichia coli Isolates from Children with Acute Diarrhea in Abuja, Nigeria

Abstract: Background: Heat-labile (LT) and heat-stable (ST) toxin variants of enterotoxigenic Escherichia coli (ETEC) are enterotoxins associated with diarrhea among children in Abuja, Nigeria. Enterotoxigenic Escherichia coli is also known as a major etiological agent of diarrheal disease among travelers in developing countries. Continuous identification of commonly expressed bacterial components of ETEC can help extend the protective spectra of future candidate ETEC vaccines in Nigeria. Objectives: This study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
2
3
2
Order By: Relevance
“…A similar finding was also reported in a study across four regions of the world and the Global Enteric Multicenter Study where ST was the most frequent toxin [ 25 , 26 ]. However, these findings are not in agreement with reports of a study in Nigeria where ST and LT toxins were detected equally among the ETEC isolates [ 8 ]. Additionally, a study in Bolivia reported that LT was the most common toxin followed by LT/ST and the least was ST. [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…A similar finding was also reported in a study across four regions of the world and the Global Enteric Multicenter Study where ST was the most frequent toxin [ 25 , 26 ]. However, these findings are not in agreement with reports of a study in Nigeria where ST and LT toxins were detected equally among the ETEC isolates [ 8 ]. Additionally, a study in Bolivia reported that LT was the most common toxin followed by LT/ST and the least was ST. [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of an identifiable CF could be explained by the following reasons; loss of plasmid harboring the CFs genes due to repeated sub culturing or long-term storage; down regulation of CF genes; a mutation within the genetic locus; expression of a CF not covered by the primers used in the PCR panel and CFs that are unknown and have not been classified [ 7 , 13 , 23 , 28 ]. The lack of CF has been reported to be mainly related to LT strains [ 8 , 13 , 27 , 32 ] which is consistent with our results where 60% of the LT strains lacked a detectable CF. However, some studies have reported that CFs is almost equally associated with LT and ST-positive ETEC strains [ 8 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations